MENUMBUHKAN KEMAMPUAN BERPIKIR LOGIS ANAK USIA DINI: STUDI PENGEMBANGAN MEDIA PERMAINAN SNAKES AND LADDERS DI TK OXFORD PURI SCHOOL PPS MANYAR GRESIK - Nina Nuriyah Ma'arif; Fifi Mazroatul Ummah (Atthiflah: Journal of Early Childhood Islamic Education, 2023)
This article reports on a study of the research and development (R&D) model regarding the development of instructional media called snakes and ladders game to foster early childhood (4-5 years old) logical thinking skills conducted at Kindergarten Oxford Puri School PPS Manyar Gresik. Using the ADDIE development model (Analyze, Design, Development, Implementation, Evaluation) promoted by Dick and Carry and descriptive quantitative analysis, the results of this study state that the game media "the snakes and ladders" is suitable for instructional media in order to stimulate and develop logical thinking skills for the early childhood. Indeed,  the validity of the media "the snakes and ladders" has revealed the "very good" category with a score of 81 (81%) reviewed by the material experts, the "very interesting" category with a score of 96 (96%) obtained from the media experts, and the category "very interesting" with score of 88 (88%) obtained from the learning practitioner experts. In addition, the trials of the products has illustrated that "the snakes and ladders" game is able to stimulate and develop children's logical thinking from "starting to develop" to "developing as expected".